Arsenic uptake in bacterial calcite. (1st February 2018) - Catelani, Tiziano; Perito, Brunella; Bellucci, Francesco; Lee, Sang Soo; Fenter, Paul; Newville, Matthew; Rimondi, Valentina; Pratesi, Giovanni; Costagliola, Pilario
Abstract: Bio-mediated processes for arsenic (As) uptake in calcite were investigated by means of X-ray Diffraction (XRD) and X-ray Absorption Spectroscopy (XAS) coupled with X-ray Fluorescence measurements. The environmental bacterial strain Bacillus licheniformis BD5, sampled at the Bullicame Hot Springs (Viterbo, Central Italy), was used to synthesize calcite from As-enriched growth media. Both liquid and solid cultures were applied to simulate planktonic and biofilm community environments, respectively. Bacterial calcite samples cultured in liquid media had an As enrichment factor (Kd) 50 times higher than that from solid media. The XRD analysis revealed an elongation of the crystal lattice along the c axis (by 0.03 Å) for biogenic calcite, which likely resulted from the substitution of larger arsenate for carbonate in the crystal. The XAS data also showed a clear difference in the oxidation state of sorbed As between bacterial and abiotic calcite. Abiotic chemical processes yielded predominantly As(V) uptake whereas bacterial precipitation processes led to the uptake of both As(III) and As(V). The presence of As(III) in bacterial calcite is proposed to result from subsequent reduction of arsenate to arsenite by bacterial activities. To the best of our knowledge, this is the first experimental observation of the incorporation of As(III) in the calcite crystal lattice, revealing a critical role of biochemical processes for the As cycling in nature.